Professional-Grade TCA-Lactic Acid Chemical Peel: Elucidating Mode of Action to Treat Photoaging and Hyperpigmentation - Bhardwaj, Vinay; Sharma, Krati; Maksimovic, Srdjan; Fan, Aixing; Adams-Woodford, Alison; Mao, Junhong (Frontiers in Medicine, 2021)
Chemical peeling is usually performed by dermatologists, plastic surgeons and aestheticians for the treatment of photo-aged skin, dyspigmented skin, skin prone to acne eruption, and pre-cancerous skin lesions, etc. In this research paper, we report our investigative findings to understand the mode of action of a commercial professional chemical peel to treat hyperpigmented and photoaged skin. In the in-vitro experiments, we found that the peel inhibits enzymes that are responsible for degradation of collagen and elastin, and the production of melanin pigment. It was surprising to observe that tricholoracetic acid (TCA), which is considered a workhorse of chemical peels for its cauterant action, could synergistically promote the inhibitory action of lactic acid. The rationale behind this synergistic effect could be the conformational change in TCA from linear structure to ring-like structure, which was elucidated through sequential docking using Rosetta software. The in-vitro results on collagen and elastin were corroborated by up-regulation of COL1A, COL3B, fibronectin, and elastin gene expression from 3D human skin equivalents treated with the peel. The findings were further validated through ex-vivo testing on human skin biopsy. The peel significantly inhibits the production of total melanin, and ameliorates photo-damage that was evident through repair of the collagen in the skin exposed to a biological effective dose of UV daily light (6 J/cm2). These research findings have implications for product developers and users (dermatologists, plastic surgeons and aestheticians) in improving safety and efficacy of chemical peels/peeling.